Temperature effects on SEI formation and cyclability of Si nanoflake powder anode in the presence of SEI-forming additives. (10th January 2017) - Haruta, Masakazu; Okubo, Takashi; Masuo, Yuta; Yoshida, Shuhei; Tomita, Akira; Takenaka, Toshio; Doi, Takayuki; Inaba, Minoru
Graphical abstract: Abstract: Silicon nanoflake powder (Si LeafPowder ®, Si-LP) used as an anode material for lithium-ion batteries has demonstrated superior cycle performance at 30 °C in an ethylene-carbonate-based electrolyte solution because its characteristic thin-film-based structure resists pulverization. However, capacity fading was accelerated at 60 °C owing to enhanced decomposition of the electrolyte solution and growth of a solid electrolyte interface (SEI), which leads to loss of the electronic contact between Si-LP particles. The SEI-forming additives vinylene carbonate (VC), fluoroethylene carbonate (FEC), and difluoroethylene carbonate improved the capacity retention and Coulombic efficiency at 30 °C. Although VC is the most effective additive at 60 °C, the discharge capacity was decreased dramatically at −5 °C owing to poor ionic and electronic conductivity of the SEI layer formed from the VC-added electrolyte solution. The added FEC produced better performance in a wide temperature range of −5 to 60 °C because the SEI layer formed in the FEC-added electrolyte solution had higher ionic and electronic conductivity than that formed from VC, even at −5 °C. To obtain Si anodes with high discharge capacity and long cycle life, an appropriate choice of SEI-forming additive taking into account the operating temperature is important.